Severity index and transfer effects on survival and volume production of Pinus sylvestris in northern Sweden - Eriksson, Gösta; Andersson, Sven; Eiche, Vilhelms; Ifver, Jan; Persson, Anders (1980)
By means of results from provenance trials in northern Sweden, a map of severity index for various latitudes and altitudes was drawn up. The severity index is defined as the expected percentage plant mortality rate in the local population during the first 20 years after establishment of the plantation. By combining transfer effects based on data from all trials, a general trend of the transfer effect was calculated. The regression obtained showed that, at constant altitude, each degree of transfer southwards meant an increase in survival of 10.8 percentage units; at constant latitude, every 100 metres of downward transfer implied an increase in survival of 3.0 percentage units. By means of a graph combining severity index with transfer effects, it is shown how optimum transfer can be estimated. Optimum transfer is defined as the transfer giving maximum volume yield, which equals 70-80 per cent survival.